Screening for Major Depressive Disorder with the Patient Health Questionnaire (PHQ-9 and PHQ-2) in an Outpatient Clinic Staffed by Primary Care Physicians in Japan: A Case Control Study - Suzuki, Keiko; Kumei, Shima; Ohhira, Masumi; Nozu, Tsukasa; Okumura, Toshikatsu (PloS one, 2015)
The Patient Health Questionnaire (PHQ-9) is a self-report questionnaire commonly used to screen for depression, with ≥8-11 generally recommended as the cut-off. In Japan, studies of the validity of the PHQ-9 and PHQ-2 have been limited. In this study, we examined the utility of the PHQ-9 and PHQ-2 at an outpatient clinic in a Medical University Hospital in Japan. New consecutive outpatients were included in the study. We administered the PHQ-9 to 574 patients, and acquired complete PHQ-9 and PHQ-2 data for 521 patients. Major depressive disorders were diagnosed according to the DSM-IV-TR. Forty-two patients were diagnosed with major depressive disorders. The mean PHQ-9 (15.7) and PHQ-2 (3.8) scores of the patients with major depressive disorders were significantly higher than the scores of the patients without depression (6.0 (PHQ-9) and 1.8 (PHQ-2)). The best cut-off points for the PHQ-9 and PHQ-2 summary scores were ≥11 (sensitivity 0.76, specificity 0.81) and ≥3 (sensitivity 0.76, specificity 0.82), respectively. No relationship was observed between the age and PHQ-9 scores. The PHQ-9 and PHQ-2 were useful instruments for screening for major depressive disorders. The best cut-off point for the PHQ-9 summary score should be ≥11 to detect depression in the primary care setting in Japan.